Comparison of Regression Equation and Friedewalds Formula with Direct Measurement of Low-density Lipoprotein Cholesterol in Bangladeshi Population - Saiedullah, M.; Chowdhury, N.; Khan, M.A.H.; Hayat, S.; Begum, S.; Rahman, M. R. (Journal of Scientific Research, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Friedewalds formula (FF) is the most widely used formula in clinical practice to calculate low-density lipoprotein cholesterol (LDLC) from total cholesterol (TC), triglyceride (TG) and high-density lipoprotein cholesterol (HDLC). But this formula frequently underestimates LDLC. The aim of this study was to derive a regression equation (RE) to abolish the underestimation and to compare the performance of RE and FF in Bangladeshi population. RE was derived from 531 lipid profiles (equation derivation group) for the calculation of LDLC by multiple linear regression analysis. The RE was then used to calculate LDLC in another 952 subjects (equation validation group). LDLC calculated by RE and FF were compared with measured LDLC by appropriate statistical analyses. In equation validation group, measured LDLC, LDLC calculated by RE and FF were 2.97±0.81, 2.91±0.80 and 2.72±0.93 mmol/L respectively. Precision (r) was 0.9525 for RE and 0.9193 for FF. Passing & Bablok linear regression equations against measured LDLC were y = 0.9792x + 0.007 for RE and y = 1.1412x 0.6781 for FF. Accuracy within ±12% of measured LDLC was 79% and 57% for RE and FF, respectively. The derived RE is more accurate than FF for the calculation of LDLC in Bangladeshi population. Keywords: Lipoprotein cholesterol; Friedewalds formula; Bangladeshi population. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i1.14864 J. Sci. Res. 6 (1), 143-152 (2014)